The role of Interpersonal Communication and Trust as antecedents of Organizational Citizenship Behavior (OCB) - Yusnita, Nancy (Jurnal Maksipreneur, 2024)
Since Organizational Citizenship Behavior (OCB) has been found to be a factor that plays an important role in achieving organizational goals and employee work productivity, a lot of research has been conducted by scholars to show this. Social exchange theory shows that the level of employee contribution is determined, in part, by the degree of trust between organizational members. The aim of this research is to find factors that play an important role in the emergence of OCB among employees. This study involves OCB, trust, and interpersonal communication. This study was conducted on production employees at a manufacturing company engaged in the production of medical equipment, totalling 114 employees using a survey method and quantitative approach, using a questionnaire as the main instrument. In this research, it was found that interpersonal communication and trust are factors that significantly influence employee OCB. Strengthening interpersonal communication and trust will increase OCB. In this research, it was also found that trust plays a role in mediating interpersonal communication and OCB. To increase OCB, organizations should first strengthen trust among employees.